Humpty Dumpty Historiography: How Historical Theorizing Missed the Linguistic Turn - Roth, Paul A. (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
The phrase “the linguistic turn” owes much of its currency in and out of historiography either to Richard Rorty’s classic 1967 anthology or John Toews’ much cited 1987 essay, each of which employs that term in their respective titles. Within historical theory particular significance has been attributed to Toews’ essay for its role in identifying a singular theoretical moment. The pervasive theoretical influence attributed to “the linguistic turn” and the role of this specific essay in heralding that moment remains undiminished. Yet despite all this attention, an important thematic connection between the two works has been missed. As a result, the most basic problem raised by the linguistic turn remains unacknowledged, hence undiscussed, and so unresolved. To appreciate why requires revisiting issues actually raised under the rubric of “the linguistic turn” and so making clear the deep thematic connections between Rorty’s anthology and Toews’ essay.